THE INFLUENCE OF WELL-FUNCTIONING PUBLIC TRANSPORT SYSTEM TO DEVELOPMENT OF TOURISM - Todorov Teodor; Švadlenka Libor (STEF92 Technology Ltd., 2015)
The improvement and modernization of transport or deterioration of transport on the other hand has a direct impact on tourism. The history of tourism and transport provides a clear understanding of this relationship. The transportation can be discussed without taking tourism into consideration but tourism can't flourish without travel. Transportation is an essential part of tourism industry. Due to the improvements of transportation the tourism industry has expanded especially during last years. This paper analyzes different structures of public transport systems and their contribution to tourism industry in the city-region, especially the contribution of public metro system. In the paper proposed metro system could have the potential for city-region to become a high profile tourism destination. In addition the metro system could ensure for the region to be more economically prosperous, less reliant on fossil fuels, more social equitable, better connected and convenient, recognizable place to invest and a place with a high standard of living and so on.
Vliv fungující veřejné dopravy na rozvoj turismu
Keywords: public transport; tourism; metro; Varna; veřejná doprava; cestovní ruch; metro; Varna